Bio-char influenced indigenous microbial stimulation for oil contaminated soil remediation in Northwest China. (3rd June 2019) - Yu, Wenhe; Zheng, Jin; Song, Quanwei; Zhao, Chaocheng; Chen, Changzhao; Chen, Hongkun; Gao, Chunyang; Song, Jiayu
Abstract: This research uses Illumina high-throughput sequencing method showing that Proteobacteria, Actinobacteria, and Fimicutes were the most influential phyla in the biodegradation process, Firmicutes and Deinococcus-Thermus were positively affected by the changes of nutrient amendments. Firmicutes can be seen as an indicator of degradation rate. Dietzia and Halomonas were the most dominant genus in Biochar and Blank degradation processes for oilfield contaminated soil in Northwest China.